2020
DOI: 10.1016/j.jtho.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sintilimab Plus Pemetrexed and Platinum as First-Line Treatment for Locally Advanced or Metastatic Nonsquamous NSCLC: a Randomized, Double-Blind, Phase 3 Study (Oncology pRogram by InnovENT anti-PD-1-11)

Abstract: Introduction: Sintilimab, an anti-programmed death 1 antibody, plus pemetrexed and platinum had revealed promising efficacy for nonsquamous NSCLC in a phase 1b study. We conducted a randomized, double-blind, phase 3 study to compare the efficacy and safety of sintilimab with placebo, both in combination with such chemotherapy (ClinicalTrials.gov: NCT03607539).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
224
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 282 publications
(241 citation statements)
references
References 22 publications
11
224
4
2
Order By: Relevance
“…In this study, sintilimab 200 mg q3w in combination with gemcitabine and cisplatin regimen was administered in treating naive patients with advanced squamous cell NSCLC until disease progression or intolerant toxicity, yielding a 64.7% (11/17) ORR, a 30% (6/17) stable disease (SD) proportion among those who have received at least one radiological assessment (42). Most recently, a randomized, double-blind, phase III study (ORIENT-11) involving 397 stage IIIB to IV non-squamous NSCLC patients with no previous systemic treatment has shown that the combination of sintilimab and pemetrexed plus platinum has led to significantly longer progression-free survival (PFS) than that of chemotherapy alone with manageable adverse effects (43). In ORIENT-11, patients received either sintilimab 200 mg or placebo plus pemetrexed and platinum q3w for 4 cycles as induction therapy, followed by sintilimab or placebo plus pemetrexed as maintenance therapy q3w for up to 24 months; although median overall survival (OS) was not reached, the median PFS, ORR, DCR were 8.9 months, 51.9% (138/266), 86.8% (231/266) in the sintilimab-combination group compared to those of 5.0 months, 29.8% (39/131) and 75.6% (99/131) in the placebo-combination group (placebo plus chemotherapy) (43).…”
Section: Efficacy Of Sintilimab In Non-small Cell Lung Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, sintilimab 200 mg q3w in combination with gemcitabine and cisplatin regimen was administered in treating naive patients with advanced squamous cell NSCLC until disease progression or intolerant toxicity, yielding a 64.7% (11/17) ORR, a 30% (6/17) stable disease (SD) proportion among those who have received at least one radiological assessment (42). Most recently, a randomized, double-blind, phase III study (ORIENT-11) involving 397 stage IIIB to IV non-squamous NSCLC patients with no previous systemic treatment has shown that the combination of sintilimab and pemetrexed plus platinum has led to significantly longer progression-free survival (PFS) than that of chemotherapy alone with manageable adverse effects (43). In ORIENT-11, patients received either sintilimab 200 mg or placebo plus pemetrexed and platinum q3w for 4 cycles as induction therapy, followed by sintilimab or placebo plus pemetrexed as maintenance therapy q3w for up to 24 months; although median overall survival (OS) was not reached, the median PFS, ORR, DCR were 8.9 months, 51.9% (138/266), 86.8% (231/266) in the sintilimab-combination group compared to those of 5.0 months, 29.8% (39/131) and 75.6% (99/131) in the placebo-combination group (placebo plus chemotherapy) (43).…”
Section: Efficacy Of Sintilimab In Non-small Cell Lung Cancermentioning
confidence: 99%
“…Most recently, a randomized, double-blind, phase III study (ORIENT-11) involving 397 stage IIIB to IV non-squamous NSCLC patients with no previous systemic treatment has shown that the combination of sintilimab and pemetrexed plus platinum has led to significantly longer progression-free survival (PFS) than that of chemotherapy alone with manageable adverse effects (43). In ORIENT-11, patients received either sintilimab 200 mg or placebo plus pemetrexed and platinum q3w for 4 cycles as induction therapy, followed by sintilimab or placebo plus pemetrexed as maintenance therapy q3w for up to 24 months; although median overall survival (OS) was not reached, the median PFS, ORR, DCR were 8.9 months, 51.9% (138/266), 86.8% (231/266) in the sintilimab-combination group compared to those of 5.0 months, 29.8% (39/131) and 75.6% (99/131) in the placebo-combination group (placebo plus chemotherapy) (43). In contrast, in a phase III study KEYNOTE-189, previously untreated patients with metastatic non-squamous NSCLC were also assigned to receive pemetrexed and platinum plus pembrolizumab (n = 410) or placebo (n = 206) q3w for 4 cycles; the median PFS, median OS, ORR, and DCR of patients in the pembrolizumab group were 9.0 and 22.0 months, 48.0% (197/410), 84.6% (347/410), compared to those of 4.9 and 10.7 months, 19.4% (40/266), 70.4% (145/206) of patients in the placebo group (44).…”
Section: Efficacy Of Sintilimab In Non-small Cell Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other programmed cell death 1 (PD-1) inhibitors or programmed cell death-ligand 1 (PD-L1) inhibitors (nivolumab, pembrolizumab and atezolizumab) approved by America Food and Drug Administration (FDA), sintilimab has been approved in China for classical Hodgkin lymphoma (8,9). Nevertheless, sintilimab alone or sintilimab plus chemotherapy has shown manageable toxicities and encouraging efficacies in several phase I-III clinical trials in NSCLC (stage IA-IIIB) patients in China (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 One such agent, sintilimab, is a humanized, monoclonal antibody against PD-1 that has received approval by the National Medical Products Administration (NMPA) for the monotherapy of relapsed or refractory classical Hodgkin lymphoma and for the treatment of unresectable, locally advanced or metastatic nonsquamous NSCLC in combination with pemetrexed and platimum. 16,17 ORIENT-2 was a randomized, open-label, phase 2 study that evaluated sintilimab versus chemotherapy in Chinese patients with advanced or metastatic ESCC refractory to rst-line chemotherapy and explored potential biomarkers for treatment e cacy.…”
mentioning
confidence: 99%